PELATIHAN MANAJEMEN PEMASARAN BAGI PETAMBAK BIBIT IKAN LAUT DI DESA BANDING-KEC. RAJABASA LAMPUNG SELATAN - M. Tony Nawawi; Darryl Darryl; Jennifer Dinata (PROSIDING SERINA, 2021)
The purpose of carrying out community service in Banding-Rajabasa Village, South Lampung, is to explain how important it is for the farmer group to know the role of knowledge about Marketing Management, and to map and provide the best solution that will be implemented in the village. "Because in this area there is still a lack of knowledge and marketing skills for these marine fish breeders", "this can be indicated by the lack of buyer visits even though the infrastructure facilities provided are adequate". "While at the implementation stage, the Pkm team provides training and assistance on Marketing Management which emphasizes aspects of sales, customer approach, communication, and marketing mix'. "For the evaluation stage, it is done by collecting data from participants regarding their understanding of the training materials, and also analyzing what they have done while developing this Banding Village related to Marketing Management capabilities". Meanwhile, the mandatory PKM output plans are Journal/Proceeding Articles, and the additional outside is in the form of h.k.i